Air pollution forecast in Portugal: a demand from the new air quality framework directive - Monteiro, A
This work aims at developing and validating a numerical air quality operational forecasting system that will be applied over Portugal. The CHIMERE model was chosen for the chemistry-transport simulation using the meteorological parameters supplied by the MM5 mesoscale meteorological model, forced by the AVN/NCEP global forecasts. An experiment of 48-hour real-time forecast simulations was performed, on a daily basis, during the four summer months of 2003. The numerical model system is then evaluated against hourly time series of basic meteorological variables and of ozone and NO(2) concentrations, collected in several Portuguese monitoring stations included in meteorological and air quality network. Statistical skill scores are discussed and compared with previous studies. The results point this developed model system as a useful tool that can be used and implemented to anticipate pollution episodes, to local and regional air quality management and for population information purpose.